2015
DOI: 10.1155/2015/357357
|View full text |Cite
|
Sign up to set email alerts
|

Naturally Occurring Anthraquinones: Chemistry and Therapeutic Potential in Autoimmune Diabetes

Abstract: Anthraquinones are a class of aromatic compounds with a 9,10-dioxoanthracene core. So far, 79 naturally occurring anthraquinones have been identified which include emodin, physcion, cascarin, catenarin, and rhein. A large body of literature has demonstrated that the naturally occurring anthraquinones possess a broad spectrum of bioactivities, such as cathartic, anticancer, anti-inflammatory, antimicrobial, diuretic, vasorelaxing, and phytoestrogen activities, suggesting their possible clinical application in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(76 citation statements)
references
References 63 publications
1
75
0
Order By: Relevance
“…Anthraquinones are a class of aromatic compound possessing a broad spectrum of bioactivities, such as cathartic, anticancer, antiinflammatory, antimicrobial, diuretic, vasorelaxing, and phytoestrogen activities [35]. In the present study, methanol extract was reported to contain anthraquinone.…”
Section: Gomathi and Shebamentioning
confidence: 66%
“…Anthraquinones are a class of aromatic compound possessing a broad spectrum of bioactivities, such as cathartic, anticancer, antiinflammatory, antimicrobial, diuretic, vasorelaxing, and phytoestrogen activities [35]. In the present study, methanol extract was reported to contain anthraquinone.…”
Section: Gomathi and Shebamentioning
confidence: 66%
“…The authentic reference compounds endocrocin (3), hypericin (5) and skyrin (6) were available from the in-house compound library of the Department of Bioorganic Chemistry, Leibniz Institute of Plant Biochemistry (IPB), Halle (Saale), Germany. Methanol and toluene were used at analytical grade.…”
Section: Reagents and Chemicalsmentioning
confidence: 99%
“…Anthraquinones represent a large family of naturally occurring pigments, which are produced by plants, microbes, lichens, insects, and fungi [1]. Besides their coloring properties, these natural products exhibit a broad range of bioactivities such as antibacterial, antiparasitic, anti-inflammatory, fungicidal, insecticidal, laxative, antiviral, and anticancer but also DNA intercalating properties [2][3][4][5][6][7]. The chemical structure of anthraquinones is based on an anthracene skeleton with two keto groups in position 9 and 10.…”
Section: Introductionmentioning
confidence: 99%
“…So far, about 200 naturally occurring AQs have been reported from lichens, fungi and higher medicinal plants (Singh and Chauhan 2004). In higher plants, they are found in some major families including Fabaceae, Polygonaceae, Rhamnaceae, Rubiaceae and Xanthorrhoeaceae (Chien et al 2015). Based on their mass spectra, about 107 phenolic compounds have been identified or tentatively characterized from the genus Rheum.…”
Section: Anthraquinonesmentioning
confidence: 99%
“…Further, kinetic, in vivo and docking studies demonstrated 17 to exhibit mixed type of inhibition that could effectively avert postprandial spikes, thereby suggesting this AQ as a potent inhibitor compared to the positive control acarbose. Though a prominent agent to intervene autoimmune diabetes (AID), Food and Drug Administration (FDA) has rendered 17 as unsafe in naturopathic treatments due to some serious side effects like diarrhea, nausea and even renal failure (Chien et al 2015). Babu et al (2004) Compound 9 was found to show a significant inhibiting action against yeast AG and was fourth best at inhibiting mammalian AG.…”
Section: Inhibits Radical Formation and Lipid Peroxidationmentioning
confidence: 99%